USING CONTRACTS IN GROUPWORK - Preston-Shoot, Michael (Groupwork, 2020)
Although regularly mentioned in the groupwork literature, contracts, as a working concept, have rarely been elaborated or explored. Yet, as research into the effectiveness of social work demonstrates, contracts form part of an identifiable, successful approach to work, which has user involvement as a central theme. This paper outlines the basics of this approach and then examines the special features of group- work as they affect the process of using contracts. The paper concludes with suggestions regarding the framework and content for working agreements with service users which are seen as morally binding on the participants. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extent searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.